A Psycholinguistic Content Analysis of Civil Service Employees’ Values Ensured by Law - Malimon, Liudmyla; Pashkina, Alla (East European Journal of Psycholinguistics, 2014)
The article deals with the value-normative regulation of professional work in the framework of state service. The concept of “values” and their impact on individual and organizational behavior of the individual has been analysed. The concept of “organizational values”, which are formed at the intersection of individual and organizational consciousness and a powerful tool for the development of organizational culture. The authors have determined that the basic sources of forming values ​​of public service employees is Ukrainian legislation , which outlines the requirements for the implementation of values ​​of professional work in this field. The psycholinguistic method of content analysis used in the study helped examine the content of a number of legislative axiological documents. The tool is an adequate procedure for the organization and carrying out of the study. It envisaged the designing of encoding matrix, scorecard, instruction encoder list (catalog) to analyze the documents. As a result of content analysis along with data factor analysis, basic values ​​of sectoral legislation in the state service have been established. The adherence to the declared values ​​is viewed as a prerequisite that the activities of civil servants correspond to legal requirements and institution charter. Personality values ​​can serve as an additional incentive to increase the organizational efficiency. References Bodrov, V. A. (2008). Sovremennyie issledovaniya fundamentalnyih i prikladnyih problem psihologii professionalnoy deyatelnosti. Psihologicheskiy Zhurnal, 29 (5), 83–90. Vlasov, P. K. (2003). Psihologiya zamyisla organizatsii. Kharkiv: Izd-vo Gumanitarnyiy tsentr, 2003. Gashenko, A. V. (2004). Vnutrishnofirmova Sistema Tsinnostey: Sotsialno-Filosofskiy Analiz [Intrafirm System of Values: Social and Philosophical analysis. Ph.D. thesis]. Zaporizhzhya. Derzhavna sluzhba v Ukrayini: Zbirnyk normatyvnykh aktiv (2002) [State Service in Ukraine]. Kyiv: Yurinkom Inter. Kagan M. S. (1974). Chelovecheskaya Deyatelnost [Human Activity]. Moscow: Politizdat. Klimov, E. A. (1994). Obschechelovecheskie tsennosti glazami psihologa-professioveda [Common human values as viewed by psychologist profession analyst]. Psihologicheskiy Zhurnal, 4, 130–136. Krasnoryadtseva, O. M. (2002). Problemy professionalnogo stanovleniya lichnosti v protsesse povysheniya kvalifikatsii. [The Issues of personality professional development during improving the qualification]. Sibirskiy Psikhologicheskiy Zhurnal, 16-17, 42–44. Malinovskiy, V. Ya. (2009). Derzhavne Upravlinnia. [State Management]. 3 rd edition. Kyiv: Atika. Shaygorodskiy, Yu. (2010). Tsinnisni orientatsiyi osobystosti: formalizovana model tsilisnogo, bagatoaspektnogo analizu [Value orientations of personality: formalized model of the integral, mulifaceted analysis]. Sotsialna Psykhologiya, 1, 94–105. Yaromich S. (2006). Organizatsiyna kultura derzhavnoyi sluzhby i imidzh derzhavnykh sluzhbovtsiv [Organization culture of state service and the image of civil servants]. Visnik NADU, 1, 111–115. Harding, S., Philips, O., Focarty, M. (1986). Contrasting Values in Western Europe. Unity, Diversity, Change. The European Value Systems Study Group. London: The Macmillian Press.